Electrocatalytic CO2 Reduction to Formate at Low Overpotentials on Electrodeposited Pd Films: Stabilized Performance by Suppression of CO Formation. Issue 7 (9th March 2017) - Zhou, Fengling; Li, Haitao; Fournier, Maxime; MacFarlane, Douglas R.
Abstract: Palladium nanoparticles are effective for catalytic CO2 reduction. However, CO, one of the most important products in the CO2 reduction sequence, has strong affinity for the Pd surface and poisons the catalytic sites rapidly. In this research, an electrodeposited Pd film exhibits high activity for CO2 reduction to formate with the suppression of CO formation at low overpotentials. The substrates, electrodeposition process and the post‐treatment of the Pd films affect the CO2 reduction pathway significantly. The cyclic voltammetry deposition produces films that exhibit more porous morphologies and have higher current efficiencies for formate than those of films produced at constant potential. These films show stable CO2 reduction performance at low overpotentials and have high current efficiencies (≈50–60 % depending on the substrate) for formate formation at a potential of −0.4 V versus the reversible hydrogen electrode without any detectable CO formation. It seems that the Pd surface generated by the new electrodeposition process described here produces a nanostructure that can promote formate formation and suppress CO formation. Abstract : Fab formate formation ! Stable electrochemical reduction of CO2 on nanostructured palladium films is achieved through the suppression of CO formation at low overpotentials, and the highest faradaic efficiency (FE) for formate is 55 % at a potential of −0.4 V versus the reversible hydrogen electrode (RHE).